Strategies and approaches in plasmidome studies—uncovering plasmid diversity disregarding of linear elements? - Dib, Julián R.; Wagenknecht, Martin; Farías, María E.; Meinhardt, Friedhelm (Frontiers in Microbiology, 2015)
The term plasmid was originally coined for circular, extrachromosomal genetic elements. Today, plasmids are widely recognised not only as important factors facilitating genome restructuring but also as vehicles for the dissemination of beneficial characters within bacterial communities. Plasmid diversity has been uncovered by means of culture–dependent or –independent approaches, such as endogenous or exogenous plasmid isolation as well as PCR-based detection or transposon-aided capture, respectively. High-throughput-sequencing made possible to cover total plasmid populations in a given environment, i.e. the plasmidome, and allowed to address the quality and significance of self-replicating genetic elements. Since such efforts were and still are rather restricted to circular molecules, here we put equal emphasis on the linear plasmids which – despite their frequent occurrence in a large number of bacteria – are largely neglected in prevalent plasmidome conceptions.